2023
DOI: 10.3390/antiox12122125
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Antioxidant Potential of Blackberry and Raspberry Leaves: Phytochemical Analysis, Scavenging Activity, and In Vitro Polyphenol Bioaccessibility

Iulia Varzaru,
Alexandra Gabriela Oancea,
Petru Alexandru Vlaicu
et al.

Abstract: The goal of this research was nutritional evaluation through the phytochemical analysis of blackberry and raspberry leaves, the screening of their biological activity (antioxidant capacity and inhibition of lipid peroxidation), and the investigation of the effect of in vitro gastrointestinal digestion (GID) of blackberry and raspberry leaves on the bioaccessibility of polyphenol subclasses. The concentrations of the analyzed liposoluble antioxidants were higher (p < 0.05) in blackberry leaves compared to ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
1
2
0
Order By: Relevance
“…This increase can be attributed to the hydrolysis of gallotannins and ellagitannins, respectively [ 56 , 61 ]. In line with our study, some authors [ 25 ] demonstrated through simulated in vitro digestion that hydroxybenzoic acids of raspberry and blackberry leaves had the highest bioaccessibility index in the intestinal phase. Gallic acid was found to be one of the most bioaccessible phenolics.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This increase can be attributed to the hydrolysis of gallotannins and ellagitannins, respectively [ 56 , 61 ]. In line with our study, some authors [ 25 ] demonstrated through simulated in vitro digestion that hydroxybenzoic acids of raspberry and blackberry leaves had the highest bioaccessibility index in the intestinal phase. Gallic acid was found to be one of the most bioaccessible phenolics.…”
Section: Discussionsupporting
confidence: 92%
“…The isomers of vitamin E were identified with a liquid chromatograph, specifically the Vanquish model manufactured by the Thermo-Electron Corporation in Waltham, MA, USA. A PDA-UV detector was utilized at a wavelength of 292 nm, following the methodology described previously by Varzaru et al [ 25 ]. The results were expressed as mg/kg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation